Vertical Integration and Corporate Strategy - Harrigan, Kathryn Rudie (Academy of Management Journal, 1985)
Proposing a new look at vertical integration and the dimensions that comprise it, this study develops a framework for predicting when firms use make-or-buy decisions. The strategic business units (SBUs) studied made fewer products and services in-house and firms were engaged in fewer stages of processing when demand was highly uncertain than they did when demand was more certain. Internal transfers from upstream or to downstream business units were more numerous when synergies with adjacent SBUs were substantial than when they were not. Some competitive imitation of vertical integration strategies occurred, and firms with high market shares sought higher ownership stakes in stages of processing adjacent to those markets.